1-Hz Bead-Pellet Injection System for Fusion Reaction Engaged by a Laser HAMA Using Ultra-Intense Counter Beams. (2nd January 2019) - Mori, Yoshitaka; Nishimura, Yasuhiko; Ishii, Katsuhiro; Hanayama, Ryohei; Kitagawa, Yoneyoshi; Sekine, Takashi; Takeuchi, Yasuki; Satoh, Nakahiro; Kurita, Takashi; Kato, Yoshinori; Kurita, Norio; Kawashima, Toshiyuki; et al.
Abstract: The injection and engagement of pellets using laser beam irradiation is one of the key technologies to realize a laser-driven inertial fusion energy (IFE) reactor. We irradiated ultra-intense laser (11 TW: 0.6 J/110 fs 2 beams with a focal intensity of 5 10 W/cm ) in counter configuration on flying 1-mm-diameter deuterated polystyrene beads beyond 600 pellets on an average at 1 Hz and 10 min per cycle for 4 years. An injection system delivers pellets with free-fall that consists of a header for pellet delivery by disk rotation and a detection unit for synchronizing the motion of a pellet for laser engagement in time. During laser irradiation, the free-falling pellet placement was at Δx = 1 mm, Δy = 0.4 mm on a plane perpendicular to the falling direction, and Δz = 0.1 mm in the falling direction at the moment of laser irradiation. Using a two-directional probe shadowgraph system, we succeeded in aligning the pellet-falling position with a laser engagement probability greater than 70%; the probability improved from the previous experiments wherein the probabilities were less than 20%. As a result, the shot probability is 27% for gamma-ray generation resulting from ultra-intense laser-matter interactions and 22% for detection of signals corresponding to fusion neutrons with a maximum yield of 4 10 n/shot. The neutron reaction induced from an integrated system of pellet injector and laser is a decisive step in the research and development of an IFE reactor.